2023
DOI: 10.1097/jcp.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine

Abstract: Background: Guidance on clozapine dosing in treatment refractory schizophrenia is based largely on data from young adult male White patients.Aim: This study aimed to audit the plasma clozapine and N-desmethylclozapine (norclozapine) concentrations attained in male and female patients of different ethnicity and smoking habit. Method:The effect of dose, sex, ethnicity, age, body weight, and smoking habit on plasma clozapine and norclozapine concentrations were studied using data from a therapeutic drug monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“… 22 Multiple publications also highlight a lower dose requirement of clozapine for females as compared with men. 23–25 These findings identify that there could be sex differences in CYP450 enzymes impacting drug metabolism. Furthermore, alterations in CYP450 enzyme phenotypes may contribute to alterations in drug metabolism that predispose patients to side effects, intolerance, and/or treatment failure.…”
Section: Discussionmentioning
confidence: 97%
“… 22 Multiple publications also highlight a lower dose requirement of clozapine for females as compared with men. 23–25 These findings identify that there could be sex differences in CYP450 enzymes impacting drug metabolism. Furthermore, alterations in CYP450 enzyme phenotypes may contribute to alterations in drug metabolism that predispose patients to side effects, intolerance, and/or treatment failure.…”
Section: Discussionmentioning
confidence: 97%
“…All of the publications supported the trend of the need for lower clozapine doses for patients of Asian ancestry and higher doses for certain African populations. 18 , 19 , 21 As an example, one of these studies predicted that a 300-mg clozapine dose would be required for patients of sub-Saharan ancestry to reach a therapeutic value (defined as 350 ng/mL), vs 220 mg for patients of European ancestry and 112 mg for patients of East Asian ancestry. 18 Potentially worrisome is that those authors also reported that patients of sub-Saharan ancestry actually had doses of clozapine similar to those of patients of European ancestry and were approximately half as likely to reach a clozapine concentration of 350 ng/mL.…”
Section: Case 1: Genetic Ancestry and Clozapinementioning
confidence: 99%